Multiferroic and Magnetoelectric Thin Films: Synthesis to Applications - K. Govind, Remya (Recent Patents on Materials Science, 2014)
The research on the application of multiferroic and magnetoelectric materials has gained momentum recently due to the exciting technological applications offered by the coupling between magnetic and electric order. In this article, an extensive review of patents on the application of multiferroic and magneto electric materials is presented. Beginning with an introduction, a brief idea of the magneto electric effect is given. Followed by the description on the different methods used for the fabrication of multiferroic single crystals and layer structures, the patents which describe the use of multiferroic and magneto electric materials for different applications are surveyed.
Keywords: magnetism